Towards donor lung recovery—gene expression changes during ex vivo lung perfusion of human lungs. Issue 6 (30th March 2018) - Yeung, Jonathan C.; Zamel, Ricardo; Klement, William; Bai, Xiao‐Hui; Machuca, Tiago N.; Waddell, Thomas K.; Liu, Mingyao; Cypel, Marcelo; Keshavjee, Shaf
Abstract : We and others have demonstrated that acellular normothermic ex vivo lung perfusion of high‐risk donor lungs can result in posttransplant outcomes equivalent to that of contemporaneous lung transplantation using standard donor lungs. However, the mechanism of this effect remains unclear. Given the restoration of cellular metabolic activity during normothermic perfusion, one possibility is that of lung healing via natural innate recovery mechanisms. We explored this by examining the gene expression changes occurring in human lungs during ex vivo lung perfusion. Human lungs clinically rejected for transplantation were perfused for 12 hours of EVLP with biopsies taken at the start, at 1 hour, at 3 hours, and then every 3 hours thereafter to 12 hours. Temporal changes were identified in 2585 genes using the Short Time‐series Expression Miner and used for pathway analysis. Despite increases in endothelial markers of inflammation, circulating leukocyte cell‐specific gene expression fell over 12 hours of ex vivo lung perfusion (EVLP), suggesting an interrupted inflammation response secondary to washout of circulating leukocytes. Analysis of these gene changes suggests lung recovery follows specific stages: cellular death, cellular preservation, cellular reorganization, and cellular invasion. EVLP may improve posttransplant lung function by washout of leukocytes and facilitating innate mechanisms of repair. Abstract : Time‐course transcriptome analysis of human lungs during ex vivo lung perfusion shows the washout of leukocytes and the potential for facilitating innate mechanisms of repair.